SAT0394 Impact of Disease Duration on Patient Reported and Clinical Outcomes in Patients with Ankylosing Spondylitis Treated with Anti-TNF: An Analysis from A Prospective, Observational Registry. (15th July 2016) - Starr, M.; Zummer, M.; Choquette, D.; Haraoui, B.; Sholter, D.; Arendse, R.; Fortin, I.; Bessette, L.; Rahman, P.; Rampakakis, E.; Psaradellis, E.; Lehman, A.J.; et al.
Abstract : Background: Previous studies have shown that treatment outcomes are affected by disease-related aspects and patient-related factors. Objectives: The aim of this analysis was to compare ankylosing spondylitis (AS) patient profiles in terms of patient characteristics and disease parameters based on disease duration and to investigate the impact of disease duration on patient reported and clinical outcomes in patients treated with anti-TNF. Methods: BioTRAC is an ongoing, prospective registry of pts initiating treatment for rheumatoid arthritis, AS, or psoriatic arthritis with infliximab (IFX) or golimumab (GLM). Eligible people for this analysis included AS patients treated with IFX and enrolled since 2005 or with GLM and enrolled since 2010. Patients were classified in three subgroups (≤1 yr, 2–10 yrs, >10 yrs) based on the tertile distribution of the time elapsed since their diagnosis. The impact of disease duration on outcomes upon adjusting for potential confounders was assessed with generalized linear models and logistic regression. Results: A total of 580 AS patients were included in this analysis with a mean age of 45.8 yrs and disease duration of 8.3 yrs. The majority were male and 92.6% were biologic naïve. At baseline, mean BASFI was 5.6, BASDAI was 6.2, and ASDAS was 3.6. With the exception of age which was significantly higher among pts with longer disease duration (P<0.001) no significant between-group differences were observed in baseline demographics and disease parameters. Upon 6 mos of treatment, clinically meaningful and statistically significant improvements were observed in BASFI, BASDAI and ASDAS which were further enhanced at 12 mos. Upon adjusting for baseline age and respective parameter levels, pts diagnosed within ≤1 yr experienced significantly lower improvements in BASFI (P=0.030), BASDAI (P<0.001), and ASDAS (P=0.030) at 12 mos as compared to pts with disease duration >10 ys. For ASDAS, concomitant DMARD use was also identified as a significant predictor of improved outcome (P=0.042). Gender and prior biologic experience did not have a significant impact on outcomes. Inactive or moderate disease activity, based on ASDAS, was achieved by 47.2% of pts while clinically important and major improvements were observed for 54.9% and 32.7% of pts, respectively. Similarly to the absolute improvements, pts diagnosed within ≤1 yr were significantly less likely to achieve these endpoints. Conclusions: The results of this real-world analysis have identified prior disease duration at anti-TNF initiation as a significant independent predictor of treatment outcome. Concomitant use of a DMARD was associated with significantly higher improvement in ASDAS. These results suggest that pts with early disease may be harder to treat and highlight the need for more aggressive treat-to-target approaches in this patient subgroup. Disclosure of Interest: M. Starr: None declared, M. Zummer: None declared, D. Choquette: None declared, B. Haraoui: None declared, D. Sholter: None declared, R. Arendse: None declared, I. Fortin: None declared, L. Bessette: None declared, P. Rahman: None declared, E. Rampakakis Employee of: JSS Medical Research Inc;, E. Psaradellis Employee of: JSS Medical Research Inc;, A. Lehman Employee of: Janssen, K. Maslova Employee of: Janssen, B. Osborne Employee of: Janssen, F. Nantel Employee of: Janssen, C. Tkaczyk Employee of: Janssen